The sub‐basal nerve plexus and central corneal stromal microstructure in subjects with congenital aniridia, using in vivo confocal microscopy - Szentmáry, Nóra; Csorba, Anita; Kormányos, Kitti; Csidey, Mária; Náray, Annamária; Kéki‐Kovács, Klaudia; Németh, Orsolya; Knézy, Krisztina; Bausz, Mária; Szigeti, Andrea; Szabó, Dorottya; Corton, Marta; et al. (Acta ophthalmologica (Oxford, England), 2024)
Purpose: Congenital aniridia is a rare disease, with a global prevalence of 1 in 40 000 to 1 in 100 000. During life up to 70% of aniridia sufferers develop aniridia‐associated keratopathy (AAK) with limbal stem cell insufficiency, impaired corneal epithelial cell differentiation, abnormal cell adhesion and wound healing. AAK is characterized by centripetal spreading vascularization, conjunctivalization, and thickening of the cornea. We examined the sub‐basal nerve plexus and central corneal stromal microstructure in subjects with congenital aniridia, using in vivo confocal laser scanning microscopy (IVCM). Methods: 31 eyes of 18 patients (55.6% males, mean age: 25.22 ± 16.35 years) with congenital aniridia and 47 eyes of 29 healthy subjects (41.4% males, mean age 30 ± 14.82 years) were examined using the Rostock Cornea Module of Heidelberg Retina Tomograph‐III. At the sub‐basal nerve plexus, corneal nerve fibre density (CNFD), corneal nerve fibre length (CNFL), corneal total branch density (CTBD) and corneal nerve fibre width (CNFW) were analysed using ACCMetrics software. Keratocyte density in the anterior, middle and posterior stroma was assessed manually. Results: The CNFD (2.02 ± 4.08 vs. 13.99 ± 6.34/mm2), CNFL (5.78 ± 2.68 vs. 10.56 ± 2.82 mm/mm2) and CTBD (15.08 ± 15.62 vs. 27.44 ± 15.05/mm2) were significantly lower in congenital aniridia subjects, than in controls (p < 0.001 for all). CNFW was significantly higher in aniridia subjects, than in controls (0.03 ± 0.004 vs. 0.02 ± 0.003 mm/mm2) (p < 0.003). Keratocyte density was significantly lower in all stromal layers of congenital aniridia subjects, than in controls (p < 0.001 for all). Stromal alterations included confluent keratocytes, keratocytes with long extensions and hyperreflective dots between keratocytes in congenital aniridia. Conclusions: CNFD, CNFL and CTBD decrease and CNFW increase well refer to the congenital aniridia associated neuropathy. The decreased keratocyte density contradicts the inflammatory hypothesis of congenital aniridia. Corneal stromal changes in different stages of AAK have to be further analysed in detail0.